Pemberdayaan Kewirausahaan Sekolah melalui Pelatihan Branding dan Website di SMAN 14 Padang - Meswantri .; Yulasmi .; Taufan Nugroho (CV. ITTC INDONESIA, 2026)
This Community Service Program (PKM) focuses on empowering members of the School Entrepreneurship Unit (UKS) at SMA N 14 Padang through training in branding, resource management, and website-based digital promotion. Limited understanding of digital brand identity, resource management, and the utilization of information technology has become a major obstacle to developing school-based entrepreneurial activities in the digital era. Through this program, participants received training in designing promotional materials using Canva AI, guidance on developing promotional websites through the LoveWebsite platform, and an introduction to the use of artificial intelligence (AI) platforms for analyzing market trends and consumer needs. In addition, participants attended resource management training covering human resource management, task allocation based on competencies, efficient resource planning, time management, and the optimization of organizational assets and digital technologies to support business sustainability. The training aimed to enhance participants' organizational management skills, strengthen teamwork, and promote data-driven decision-making. The implementation methods included socialization, technical training, hands-on mentoring, practical resource management planning, and evaluation based on attendance, participation, and mastery of the training materials. The results demonstrated significant improvements in participants' knowledge and skills, particularly in developing digital brand identities, managing organizational resources effectively, creating professional visual promotional content, and establishing an online presence through the official UKS website. This program is expected to improve the competitiveness of the School Entrepreneurship Unit while contributing to sustainable, innovative, and competitive local economic development in the digital era.